Relationship between Industry-level dynamic capabilities and competitive advantage of Nigerian SMEs - Christopher Idemudia Ebegbetale; Samuel Essien Okon (Universitas Trisakti, 2022)
SMEs are the main engine of economic growth and development after oil and gas sector in Nigeria. However more than 50% of them fail within the first three years of their formation owing to the complex and rapidly changing business environment. The role of dynamic capability in addressing these trends and sustaining firm’s performance is a contentious issue among scholars. Therefore, this study examines the relationship between dynamic capabilities and competitive advantage among SMEs in Lagos, Nigeria. Three hypotheses were formulated and tested using correlation and regression statistical techniques on data collected from 400 study participants through questionnaire survey design and simple random sampling technique. The correlation analysis showed no significant relationship between adaptive capability competitive advantage (r = .001; p>0.01). However, the correlation result showed absorptive capability have a significant positive relationship with competitive advantage (r = .389; p<0.01); and same for innovative capability and competitive advantage (r = .307; p<0.01). The regression analysis showed that each of the three dimensions made statistical significant contribution to the predictive variable. The regression analysis further showed that the predictor variable (dynamic capability) contribute 27% to competitive advantage among SMEs in Lagos. The study suggested that firms should identify which dimension of dynamic capability will enhance and sustain their competitive advantage as the relevance of each dimension vary among firms and industries.